Method for preparing single-walled carbon nanotubes

By using high melting point metal nanoparticles and continuous gas phase processes, the chirality of SWCNT was successfully controlled, the problem of difficulty in chiral control in the prior art was solved, the narrow size distribution and specific chiral growth of SWCNT were achieved, and its performance in electronic devices was improved.

CN114929620BActive Publication Date: 2025-03-18CAMBRIDGE ENTERPRISE LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202080084066.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-12-03
Filing Date
2020-11-25
Publication Date
2025-03-18
Estimated Expiration
2040-11-25

AI Technical Summary

Technical Problem

The difficulty in effectively controlling the chirality of single-walled carbon nanotubes (SWCNTs) has led to the inadequate utilization of its potential in next-generation transistors and sensors.

Method used

By using high melting point metal nanoparticles, near monodispersed metal nanoparticles are produced using a continuous gas phase process and introduced into a temperature controlled reactor, co-exposed with the carbon source to a specific temperature zone to grow SWCNTs with narrow controlled chirality.

Benefits of technology

Effective control of SWCNT chirality is achieved, and SWCNT with narrow size distribution and specific chirality is grown, improving its performance and application potential in electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114929620B_ABST
    Figure CN114929620B_ABST
Patent Text Reader

Abstract

The present invention relates to the production of carbon materials (eg, carbon nanomaterials) comprising single-walled carbon nanotubes (SWCNTs), as well as the carbon materials themselves.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the production of carbon materials (eg, carbon nanomaterials) comprising single-walled carbon nanotubes (SWCNTs), as well as the carbon materials themselves. Background Art

[0002] The potential of SWCNTs to realize their promise in next-generation transistors and sensors has been hampered by a lack of control over their chirality. Although control of chirality has been achieved on a laboratory scale by wet selective purification, this inevitably destroys the pristine SWCNTs.

[0003] For this reason, direct chemical deposition (CVD) is the preferred production method.However, even after decades of research, the direct growth of SWCNTs with a narrow chirality distribution remains challenging.

[0004] During CVD, it is widely accepted that the structure and morphology of the catalyst particles play a decisive role in the properties of CNTs. For example, the Ostwald ripening and flexible morphology of traditional liquid catalysts (such as iron, cobalt and nickel) mean that direct control of chirality is still unavailable. Alternatively, catalysts that are always solid during growth retain the hope of achieving in-situ chirality control. It has been suggested that the higher energy barrier of solid catalysts to incorporation of new carbon atoms can be used as a control method (see Artyukhov, VI, Penev, ES & Yakobson, BI Why nanotubes grow chiral. Nat. Commun. 5, 4892, doi: 10.1038 / ncomms5892).

[0005] Methods for large-scale generation of small, precisely controlled nanoparticles are another long-sought goal. Due to the correlation between SWCNT diameter and catalyst diameter, controlling chirality can be directly linked to the easy production of solid catalysts with narrow size distribution. Recent methods for producing solid catalysts either use molecular clusters with fixed metal ratios (see Yang, F. et al. Chirality-specific growth of single-walled carbon nanotubes on solid alloy catalysts. Nature 510, 522, doi: 10.1038 / nature13434), or use special substrates (substrate, substrate) reaction restrictions (see Zhang, S. et al. Arrays of horizontal carbon nanotubes of controlled chirality grown using designed catalysts. Nature advance online publication, doi: 10.1038 / nature21051). A scale-up method without substrate restrictions will greatly benefit the industrialization of chirality-controlled SWCNT production. Summary of the invention

[0006] The present invention seeks to improve the continuous or semi-continuous production of single-walled carbon nanotubes (SWCNTs) by using high-melting-point metal nanoparticles prepared in nearly monodisperse sizes by a continuous gas phase (aerosol) process. In particular, monodisperse metal nanoparticles can be fed into a reactor or deposited onto a substrate and used to successfully grow random or aligned SWCNTs with narrowly controlled chirality.

[0007] Thus, viewed from a first aspect, the invention provides a method for producing a carbon material comprising SWCNTs, wherein the method comprises:

[0008] (a) generating a stream of a refractory metal material suspended in a carrier gas;

[0009] (b) introducing a stream of the refractory metal material into a temperature-controlled flow-through furnace;

[0010] (c) subjecting the stream of refractory metallic material to temperatures sufficient to generate a stream of refractory metallic material, wherein the stream of refractory metallic material is exposed to a first temperature zone sufficient to vaporize the refractory metallic material and a second temperature zone downstream of the first temperature zone, wherein the second temperature zone is sufficient to re-nucleate the refractory metallic material to generate the stream of nanoparticulate refractory metallic material;

[0011] (d) separating a discrete flow of nanoparticulate refractory metal material exhibiting a selected nanoparticle size distribution from the flow of nanoparticulate refractory metal material;

[0012] (e) introducing the discrete stream of the nanoparticulate refractory metal material into a temperature controlled reactor;

[0013] (f) optionally, releasing a stream of a reducing agent into the temperature controlled reactor, wherein the stream of reducing agent and the discrete stream of nanoparticulate refractory metal material are exposed to a third temperature zone sufficient to generate a stream of nanoparticulate refractory metal;

[0014] (g) releasing a stream of a carbon source into the temperature-controlled reactor; and

[0015] (h) exposing the nanoparticulate refractory metal and carbon source to a fourth temperature zone sufficient to produce a SWCNT-containing carbon material that is adaptable into a supported or self-supporting form or that can be collected from the temperature-controlled reactor.

[0016] The flow (or each flow) may be an aerosol flow.

[0017] The refractory metal material may be suspended in a carrier gas as solid particles, preferably solid nanoparticles. The refractory metal material may be formed into a powder dispersion.

[0018] The refractory metal material may be a refractory metal element (eg, refractory metal element powder) or a refractory metal compound.

[0019] The refractory metal compound may be a refractory metal complex, a salt or an organometallic compound.

[0020] The carrier gas is typically one or more of nitrogen, argon, helium or hydrogen. Preferably, the carrier gas is nitrogen.

[0021] Preferably, step (a) comprises:

[0022] (a') atomizing a liquid formulation of the refractory metal compound.

[0023] The liquid preparation may be a slurry. The liquid preparation may be an aqueous preparation. The liquid preparation may be a solution, a dispersion or a suspension. Step (a') may be performed in a sprayer.

[0024] In a preferred embodiment, the liquid formulation of the refractory metal compound is a refractory metal salt solution. Particularly preferably, the refractory metal salt solution is very dilute. The use of very dilute refractory metal salt solutions allows for easy and accurate control of the particle size of the nano-particulate refractory metal material discharged from the temperature controlled flow-through furnace.

[0025] The concentration of the refractory metal salt solution may be 1.0 mM or less (relative to metal atoms), preferably 0.7 mM or less, particularly preferably 0.3 mM or less.

[0026] Preferably, step (a) further comprises:

[0027] (a") drying the stream of refractory metal compound.

[0028] Step (a") may be carried out by a desiccant dryer.

[0029] Steps (a') and (a") can be carried out together by spray drying.

[0030] Step (a) can be performed using a hot wire (hot wire mesh).

[0031] Preferably, step (a) comprises:

[0032] (a1) Dispersing a flow of refractory metal material in a carrier gas.

[0033] Step (a1) can be carried out in a fluidized bed feeder, a jet mill or a positive displacement-style feeder.

[0034] The refractory metal substance may be a refractory metal element.

[0035] Preferably, the refractory metal material is a refractory metal oxide.

[0036] Preferably, step (f) is releasing a stream of reducing agent into the temperature controlled reactor, wherein the stream of reducing agent and the discrete stream of nanoparticulate refractory metal material are exposed to a third temperature zone sufficient to generate a stream of nanoparticulate refractory metal.

[0037] The reducing agent may be hydrogen.

[0038] The carbon material may comprise multi-walled carbon nanotubes (e.g. double-walled carbon nanotubes). Typically, the carbon material is mainly SWCNTs. The SWCNTs may be high-purity SWCNTs. The amount of SWCNTs in the carbon nanotubes is typically >50%. Preferably, the amount of SWCNTs in the carbon nanotube structure is >80%, particularly preferably >90%, and more preferably >95wt%.

[0039] Preferably, in the carbon material comprising SWCNTs, most of the SWCNTs exhibit one or more pairs of chiral indices selected from (2n±2,n), (2n±1,n), and (2n,n). Particularly preferably, in the carbon material comprising SWCNTs, most of the SWCNTs exhibit a pair of chiral indices of (2n,n).

[0040] Typically, the chiral index pairs are determined by Raman spectroscopy of the carbon material in the radial breathing mode region.

[0041] Preferably, n is an integer in the range of 4-7, particularly preferably in the range of 5-7.

[0042] The chiral index pair may be (12,6), (10,5), (8,4), (12,5) or (9,4).

[0043] Preferably, the chiral index pair is (12,6) and / or (10,5).

[0044] Preferably, the chiral index pair is (12, 6).

[0045] Preferably, 50 wt % or more of the SWCNTs, particularly preferably 60 wt % or more of the SWCNTs, more preferably 75 wt % or more of the SWCNTs, still more preferably 85 wt % or more of the SWCNTs, especially preferably 90 wt % or more of the SWCNTs exhibit one or more chiral index pairs selected from (2n±2,n), (2n±1,n) and (2n,n).

[0046] Preferably, in the carbon material comprising SWCNTs, most of the SWCNTs exhibit a chiral angle in the range of 12 to 26° (preferably 13 to 24°, particularly preferably 16 to 22°, more preferably 17 to 21°, still more preferably 18 to 20°).

[0047] Preferably, 50 wt % or more of the SWCNTs, particularly preferably 60 wt % or more of the SWCNTs, more preferably 75 wt % or more of the SWCNTs, still more preferably 85 wt % or more of the SWCNTs, especially preferably 90 wt % or more of the SWCNTs exhibit a chiral angle in the range of 12 to 26°.

[0048] Preferably, in the carbon material including SWCNTs, an average chiral angle of the SWCNTs is in the range of 18 to 20°.

[0049] The refractory metal may have a melting point in excess of 2500°C.

[0050] The refractory metal may be one or more of the group consisting of W, Mo, Re, V, Nb, Ir, Ru, Os, and Rh.

[0051] Preferably, the refractory metal is W, Mo or Re. Particularly preferably, the refractory metal is W. Particularly preferably, the refractory metal is Mo. Particularly preferably, the refractory metal is Re.

[0052] In step (h), the nanoparticulate refractory metal may act as a catalyst in its elemental form. Alternatively, the nanoparticulate refractory metal may react with carbon to form a nanoparticulate refractory metal carbide that acts as a catalyst.

[0053] The first temperature zone may be 250° C. or higher, preferably 500° C. or higher, particularly preferably 950° C. or higher.

[0054] The second temperature zone may be at a temperature lower than the temperature of the first temperature zone. The second temperature zone may be in the temperature controlled flow-through furnace, or located downstream of the temperature controlled flow-through furnace. The second temperature zone may be a cooling zone.

[0055] The third temperature zone may be at 200° C. or higher.

[0056] The fourth temperature zone may be 500° C. or higher, preferably 700° C. or higher.

[0057] Preferably, step (d) is performed by classifying the nanoparticles of the nanoparticulate refractory metal substance according to their mass, aerodynamic diameter or electrical mobility.

[0058] Step (d) can be performed by a particle size classifier (eg, an aerosol classifier), which can be a differential mobility analyzer, an aerodynamic aerosol classifier, or a centrifugal particle mass analyzer.

[0059] The geometric mean diameter GMD (e.g., mobility diameter) of the nanoparticulate refractory metal material in the discrete stream of nanoparticulate refractory metal material may be 10 nm or less, preferably 7 nm or less, particularly preferably 3 nm or less. The geometric mean diameter (GMD) of the nanoparticulate refractory metal material in the discrete stream of nanoparticulate refractory metal material may be in the range of 1 to 5 nm.

[0060] The number concentration of the nano-particulate refractory metal material in the discrete flow of the nano-particulate refractory metal material may be 10 5 cm -3 or higher, preferably 106 cm -3 or higher, particularly preferably 10 7 cm -3 or higher.

[0061] Preferably, the nanoparticulate refractory metal material in the discrete stream of nanoparticulate refractory metal material is substantially monodisperse. Preferably, the geometric standard deviation (GSD) of the diameter (e.g., mobility diameter) of the nanoparticulate refractory metal material is less than 2, particularly preferably less than 1.5, and more preferably less than 1.1.

[0062] The geometric mean diameter (GMD) of the nanoparticulate refractory metal may be 8 nm or less, preferably 5 nm or less, particularly preferably 2 nm or less. The geometric mean diameter (GMD) of the nanoparticulate refractory metal may be in the range of 1 to 5 nm.

[0063] Preferably, the method further comprises:

[0064] (e') introducing a second discrete stream of nanoparticulate refractory metal material into the temperature controlled reactor.

[0065] The separated stream of the second nanoparticulate refractory metal material may be prepared by subjecting the second refractory metal material to steps (a) to (d), or together with steps (a) to (d) being performed on the refractory metal material, or separately from steps (a) to (d) being performed on the refractory metal material. For example, steps (a) to (d) may be performed on the refractory metal compound and the second refractory metal compound together, either as a mixture or as an alloy or intermetallic compound.

[0066] The second refractory metal compound may be a W, Mo, Re V, Nb, Ir, Ru or Rh compound.

[0067] In supported form, the carbon material comprising SWCNTs can be supported (eg, deposited) on a substrate.

[0068] In a self-supporting form, the carbon material comprising SWCNTs can be a powder, fiber, film, or mat.

[0069] The carbon material containing SWCNTs can be collected from the temperature controlled reactor by discharging the carbon material containing SWCNTs as a continuous discharge through the discharge outlet of the temperature controlled flow-through reactor and collecting the continuous discharge. The carbon material containing SWCNTs can be discharged by mechanical, electrostatic or magnetic forces. The continuous discharge can be collected mechanically. For example, the continuous discharge can be collected on a rotating spindle or drum.

[0070] The flow rate of the discrete stream of nanoparticulate refractory metal material in step (e) may be up to 50 g / hour (eg, about 7 g / hour).

[0071] In step (e), the nano-particulate refractory metal material can be introduced (e.g., injected) in a linear flow, axial flow, eddy flow, spiral flow, laminar flow, or turbulent flow channel. The nano-particulate refractory metal material can be introduced at multiple locations. In step (e), the nano-particulate refractory metal material can be introduced into a temperature-controlled flow-through reactor in an axial manner or a radial manner (via a probe or a syringe).

[0072] Prior to step (g), the carbon source may be heated. Prior to step (g), the carbon source may be subjected to radiative heat transfer by infrared, visible, ultraviolet, x-ray, radio frequency or microwave energy.

[0073] In step (g), the carbon source may be introduced (eg, injected) in a linear flow, axial flow, vortex flow, spiral flow, laminar flow, or turbulent flow channel.

[0074] In step (g), the carbon source may be introduced into the temperature controlled flow-through reactor in an axial or radial manner. The carbon source may be introduced in an axial manner via a probe or a syringe. The carbon source may be introduced at multiple locations.

[0075] The carbon source may be an optionally substituted and / or optionally hydroxylated aromatic or aliphatic, acyclic cyclic hydrocarbon (e.g. alkyne, alkane or alkene), which is optionally interrupted by one or more heteroatoms (e.g. oxygen). Preferred are optionally halogenated C 1-6 A hydrocarbon (e.g. methane, propane, ethylene, acetylene or tetrachloroethylene), an optionally mono-, di- or tri-substituted benzene derivative (e.g. toluene), or C 1-6 Alcohol (eg ethanol).

[0076] Preferably, the carbon source is methane, optionally (but preferably) in the presence of optionally substituted and / or optionally hydroxylated aromatic or aliphatic, acyclic or cyclic hydrocarbons (e.g. alkynes, alkanes or alkenes) optionally interrupted by one or more heteroatoms (e.g. oxygen).

[0077] The carbon source may be C 1-6 Hydrocarbons such as methane, ethylene or acetylene.

[0078] The carbon source may be an alcohol, such as ethanol or butanol.

[0079] The carbon source may be an aromatic hydrocarbon, such as benzene or toluene.

[0080] In a preferred embodiment, the carbon source is methane, optionally in the presence of propane or acetylene.

[0081] The flow rate of the carbon source may be in the range of 0.5 to 30,000 sccm (eg, 2,000 sccm).

[0082] Typically, in step (g), the carbon source is introduced along with a carrier gas such as helium, hydrogen, nitrogen or argon.

[0083] The temperature controlled flow-through reactor and / or the temperature controlled flow-through furnace may be cylindrical or of other geometrical shapes.The temperature controlled flow-through reactor and / or the temperature controlled flow-through furnace may be substantially vertical or horizontal.

[0084] The walls of the temperature controlled flow-through reactor and / or temperature controlled flow-through furnace may be selectively cooled by exposure to a cooling fluid such as water, liquid nitrogen, or liquid helium.

[0085] The temperature controlled flow reactor and / or the temperature controlled flow furnace may be adapted to provide an axial temperature gradient. The axial temperature gradient may be non-uniform (e.g., step-wise). The temperature controlled flow reactor and / or the temperature controlled flow furnace may be resistively heated, plasma or laser controlled. The temperature profile in the temperature controlled flow reactor and / or the temperature controlled flow furnace may be substantially parabolic.

[0086] The temperature controlled flow-through reactor and / or temperature controlled flow-through furnace may be adapted to introduce reactants (eg, via an injection nozzle, lance, probe, or multi-orifice injector (eg, showerhead injector)).

[0087] Viewed from a second aspect, the invention provides an assembly for producing a carbon material comprising SWCNTs, wherein the assembly comprises:

[0088] (A) an aerosolization device for generating an aerosol flow of a refractory metal material suspended in a carrier gas;

[0089] (B) a temperature controlled flow-through furnace operatively connected to the aerosolization device and located downstream of the aerosolization device, wherein in use the temperature controlled flow-through furnace receives a flow of the refractory metal material and discharges a flow of nanoparticulate refractory metal matter;

[0090] (C) a particle size classifier operatively connected to and downstream of the temperature controlled flow-through furnace, wherein, in use, the particle size classifier separates discrete streams of nanoparticulate refractory metal material according to a selected particle size distribution; and

[0091] (D) a temperature-controlled reactor operatively connected to the particle size classifier and located downstream of the particle size classifier, wherein, in use, the temperature-controlled reactor receives a discrete flow of the nanoparticulate refractory metal material, an optional flow of a reducing agent, and a flow of a carbon source, thereby producing a carbon material comprising SWCNTs.

[0092] In this aspect of the invention, the steps and features may be as defined above for similar steps and features.

[0093] Viewed from a still further aspect, the present invention provides a process for producing a carbon material comprising SWCNTs, wherein the process comprises:

[0094] (1) generating a flow of refractory metal material suspended in a carrier gas;

[0095] (2) introducing a flow of the refractory metal material into a temperature-controlled flow furnace;

[0096] (3) subjecting the stream of refractory metal material to temperatures sufficient to generate a stream of refractory metal material, wherein the stream of refractory metal material is exposed to a first temperature zone sufficient to vaporize the refractory metal material and a second temperature zone downstream of the first temperature zone, wherein the second temperature zone is sufficient to re-nucleate the refractory metal material to generate a stream of nanoparticulate refractory metal material;

[0097] (4) separating a discrete stream of nanoparticulate refractory metal material exhibiting a selected nanoparticle size distribution from the stream of nanoparticulate refractory metal material;

[0098] (5) exposing the optional reducing agent and the flow of the nanoparticulate refractory metal material to a third temperature zone sufficient to produce the nanoparticulate refractory metal; and

[0099] (6) exposing the carbon source and the nanoparticulate refractory metal to a fourth temperature zone sufficient to produce the SWCNT-containing carbon material,

[0100] The process further comprises depositing the nanoparticulate refractory metal material onto a substrate after step (4) or depositing the nanoparticulate refractory metal onto a substrate after step (5).

[0101] In this aspect of the invention, the steps and features may be as defined above for similar steps and features.

[0102] Viewed from a still further aspect, the present invention provides an apparatus for producing a carbon material comprising SWCNTs, wherein the apparatus comprises:

[0103] (A) an aerosolization device for generating an aerosol flow of a refractory metal material suspended in a carrier gas;

[0104] (B) a temperature controlled flow-through furnace operatively connected to the aerosolization device and located downstream of the aerosolization device, wherein, in use, the temperature controlled flow-through furnace receives a flow of the refractory metal material and discharges a flow of nanoparticulate refractory metal matter;

[0105] (C) a particle size classifier operatively connected to and downstream of the temperature controlled flow-through furnace, wherein, in use, the particle size classifier separates discrete streams of nanoparticulate refractory metal material according to a selected particle size distribution;

[0106] (D) a first means for exposing an optional reducing agent and said nanoparticulate refractory metal material to a temperature sufficient to produce the nanoparticulate refractory metal; and

[0107] (E) a second means for exposing a carbon source and the nanoparticulate refractory metal to a temperature sufficient to produce the SWCNT-containing carbon material,

[0108] The apparatus further comprises: a precipitator, which is either operatively connected to the particle size classifier and located downstream of the particle size classifier, wherein when in use, the precipitator deposits the nano-granular refractory metal material onto a substrate, or is operatively connected to the first device and located downstream of the first device, wherein when in use, the precipitator deposits the nano-granular refractory metal onto a substrate.

[0109] In this aspect of the invention, the steps and features may be as defined above for similar steps and features.

[0110] In a preferred embodiment, the precipitator is an electrostatic precipitator.

[0111] Viewed from an even still further aspect, the present invention provides a carbon material comprising SWCNTs, wherein a majority of the SWCNTs exhibit chiral index pairs selected from (2n±2,n), (2n±1,n) and (2n,n).

[0112] Typically, the chiral index is determined by Raman spectroscopy performed on the carbon material in the radial breathing mode region.

[0113] Preferably, in the carbon material comprising SWCNTs, most of the SWCNTs exhibit a chiral index pair of (2n, n).

[0114] Preferably, n is an integer in the range of 4 to 7, particularly preferably in the range of 5 to 7.

[0115] The chiral index pair may be (12,6), (10,5), (8,4), (12,5) or (9,4).

[0116] Preferably, the chiral index pair is (12,6) and / or (10,5).

[0117] Preferably, the chiral index pair is (12, 6).

[0118] Preferably, 50 wt % or more of the SWCNTs, particularly preferably 60 wt % or more of the SWCNTs, more preferably 75 wt % or more of the SWCNTs, still more preferably 85 wt % or more of the SWCNTs, especially preferably 90 wt % or more of the SWCNTs exhibit one or more chiral index pairs selected from (2n±2,n), (2n±1,n) and (2n,n).

[0119] From an even further aspect, the present invention provides a carbon material comprising SWCNTs, wherein a majority of the SWCNTs exhibit a chiral angle in the range of 12 to 26° (preferably 13 to 24°, particularly preferably 16 to 22°, more preferably 17 to 21°, still more preferably 18 to 20°).

[0120] Preferably, 50 wt % or more of the SWCNTs, particularly preferably 60 wt % or more of the SWCNTs, more preferably 75 wt % or more of the SWCNTs, still more preferably 85 wt % or more of the SWCNTs, especially preferably 90 wt % or more of the SWCNTs exhibit a chiral angle in the range of 12 to 26°.

[0121] From a further aspect, the present invention provides a carbon material comprising SWCNTs, wherein the average chiral angle of the SWCNTs is in the range of 18 to 20°. BRIEF DESCRIPTION OF THE DRAWINGS

[0122] The present invention will now be described in a non-limiting sense with reference to the following accompanying drawings, in which:

[0123] Figure 1 A schematic illustration of aerosol generation and a size selection setup for sequential nanoparticle production and collection, and a diagram of mobility-equivalent diameters taken at various stages of the method of the invention;

[0124] Figure 2 ac are AFM images of W oNPs uniformly deposited on SiO2 / Si substrates. A population of particles with a narrow size distribution is shown, with various average diameters, including (a) ~1.2 nm, (b) ~2.0 nm, and (c) ~3.2 nm;

[0125] Figure 2 de are HRTEM images of: (d) polycrystalline Mo oNPs with a mobility-equivalent diameter of 10 nm, corresponding to a diameter of ∼7 nm measured by TEM, and (e) single crystalline Mo mNPs after reduction and reconstruction. The diameter of the mNPs is ∼60% of the oNP diameter;

[0126] Figure 2 f shows the evolution of the diameter observed for several mobility-equivalent diameters as Mo NPs pass through the stages of particle generation and CNT growth, as demonstrated using DMA. The black arrows demonstrate Figure 2 The diameter decreases by ∼60% between d and e. During the growth phase, Mo2C maintains the size of the mNPs, which significantly determines the diameter of the CNTs;

[0127] Figure 3 ab show SEM images of SWCNTs grown from (a) low areal density NPs and (b) high areal density NPs on labeled SiO2 / Si substrates;

[0128] Figure 3 c shows the XRD profiles of W, Mo and Re catalysts during the growth stage (all nanoparticles were supported on alumina filters);

[0129] Figure 3 de shows TEM images of SWCNTs grown with (d) 2.4 nm Mo oNPs and (e) 4.3 nm W oNPs;

[0130] Figure 3 f shows the TEM image of SWCNTs grown with 6.7 nm Mo oNPs. Producing few-walled CNTs with more defects;

[0131] Figure 4 ac are the Raman mapping results of SWCNTs grown from W catalyst (oNP diameter ∼2.5 nm, mNP diameter ∼1.5 nm). Raman spectra in the RBM region were detected by (a) 532 nm, (b) 638 nm, and (c) 785 nm lasers, where all baselines were subtracted;

[0132] Figure 4 d to f are the mass abundance statistics from 532, 638, and 785 nm lasers, respectively, where the scale is normalized;

[0133] Figure 4 g is the mass abundance statistics shown on the graphene map in the diameter range of 0.65-2 nm;

[0134] Figure 4h is a graphene map summarizing the abundance results from electron diffraction identification;

[0135] Figure 4 i is the electron diffraction pattern of the (12,5) tube (left: experiment, right: simulation);

[0136] Figure 5 Schematic diagram of the floating catalyst CVD (FCCVD) setup and the corresponding preliminary results of CNTs grown from FCCVD without size selection;

[0137] Figure 6 is a refted Kataura diagram of a portion of a SWCNT array grown directly on a SiO2 / Si substrate. The 532nm, 638nm, and 785nm laser resonance regions are marked with dashed lines, and the broadening factor is set to 100meV for each;

[0138] Figure 7 Displays the concentration of the nebulized solution and Figure 1 Relationship between (a) mean diameter (GMD), (b) standard deviation (GSD), and (c) concentration of oNPs measured at position IV.

[0139] Figure 8 XRD patterns of (a) W, (b) Mo, and (c) Re nanoparticles and (d) Re nanoparticles formed in the presence of a carbon source are shown;

[0140] Fig. 9 a and b are TEM images showing that SWCNTs form aligned arrays when grown from NPs deposited on (a) sapphire and (b) quartz substrates under atomic (atom) step guidance. Inset is the FFT of (a);

[0141] Fig.10 is a schematic illustration of a DMA column;

[0142] Fig.11 al shows mass abundance statistics from Raman mapping in the RBM region of SWCNTs grown from (ad) W~2.8nm oNPs, (eh) Mo~2.5nm oNPs, and (il) Re~3.0nm oNPs, detected by (aei) 532nm, (bfj) 638nm, and (cgk) 785nm lasers, respectively. All results are normalized to scale and presented on (dhl) graphene maps in the 0.65-2nm diameter range;

[0143] Fig.12Results of Raman mapping and abundance statistics of low carbon growth (C / FI ∼ 6) of SWCNTs from Mo mNPs (∼ 1.5 nm) are shown;

[0144] Fig.13 a to 13c show HRTEM images of carbon-masked catalysts and short CNTs (~2.6 nm) from W mNPs;

[0145] Fig.13 d to 13f show HRTEM images of carbon-masked catalyst and short CNTs (~4.5 nm) from MomNPs; and

[0146] Fig.14 Quantitative calculations of abundance based on different factors are shown: (a) SWCNT abundance from liquid catalysts, considering only nucleation thermodynamic factors (SWCNTs are concentrated near the armchair region); (b) SWCNT mass abundance from liquid catalysts, considering only growth kinetic factors based on screw dislocation theory (the growth rate of SWCNTs is proportional to the chiral angle); (c) SWCNT mass abundance from liquid catalysts, considering both factors from (a) and (b) (the preferred region is near the armchair chirality, but experiments show that the abundance is mainly determined by the growth rate in (b) and leads to a wider distribution of chirality with large chiral angles); (d) SWCNT mass abundance from solid catalysts, considering only nucleation thermodynamic factors, based on reported interfacial energy values ​​(SWCNTs are concentrated in the zigzag region). region); (e) SWCNT mass abundance from solid catalysts, considering only growth kinetics (the growth rate will reach its maximum near the chiral angle of 19.1°); (f) SWCNT mass abundance from solid catalysts, considering both factors from (d) and (e) (chirality is preferred to be near the zigzag, as reported by Penev, ES, Bets, KV, Gupta, N. & Yakobson, BI Transient Kinetic Selectivity in Nanotubes Growth on Solid Co-W Catalyst. Nano Letters 18, 5288-5293, (2018), where the interfacial energy values ​​are the same); (g) SWCNT mass abundance from solid catalysts, considering the SWCNT diameter size guidance from its catalyst (the distribution will be more concentrated). A normal distribution with an average diameter of 1.2 nm and a standard deviation of 0.3 nm is used, such as Figure 2a; (h) SWCNT mass abundance from solid catalyst, taking into account the chirality-dependent growth time (by growing SWCNTs in a carbon-rich environment, the chirality-dependent growth time factor leads to a higher abundance concentration near (2n,n), with a threshold set to poison ~1 / 2 of the catalysts); (i) SWCNT mass abundance from solid catalyst, where the catalyst distribution is narrow and the size is fine (0.8±0.2nm), where ~1 / 4 of the catalysts are poisoned (semiconducting chiralities such as (8,4), (10,3), (9,4) and (11,3) are expected to be enriched). (Modeling was performed for all chiralities with diameters between 0.65 and 2 nm and T = 850 °C. For liquid catalysts, the CNT-catalyst interaction energy values ​​for A or Z edge atoms are 0.09 eV / atom and 0.345 eV / atom, respectively, which are reported for Co(111) catalysts with segregated A|Z interfaces (see Bets, KV, Penev, ES & Yakobson, BI Janus Segregation at the Carbon Nanotube-Catalyst Interface. ACS Nano, (2019)).) For solid catalysts, respectively is 0.147 eV / atom and is 0.144 eV / atom, which was reported for a Co7W6 solid catalyst in which the W slabs have separated A|Z interfaces (see Bets et al. [supra]). DETAILED DESCRIPTION

[0147] Example

[0148] This example relates to embodiments of the invention in which there is a continuous gas phase production of a size-selective, high melting point catalyst for SWCNT chirality control.Three refractory metals were investigated: tungsten (W), molybdenum (Mo), and rhenium (Re). Figure 1 Schematic illustration of aerosol generation and the size selection setup for sequential nanoparticle production and collection, and plots of mobility-equivalent diameters taken at various stages.

[0149] (NH4)6H2W was prepared at a concentration of 0.3 mM relative to the metal atom. 12 O 40 (Sigma-Aldrich463922), (NH4)6Mo7O 24(Sigma-Aldrich 09878) and NH4ReO4 (Sigma-Aldrich 316954) were each prepared in highly diluted aqueous metal salt solution. The highly diluted aqueous solution was atomized into droplets suspended in nitrogen using a TSI Inc. 9302 atomizer at a flow rate of 3.6 slpm. The resulting micro-droplet mist ( Figure 1 The mist is passed through a desiccant dryer where the water is removed to leave the precipitated metal salt nanoparticles (sNPs) suspended in a carrier gas as an aerosol ( Figure 1 The metal SNPs are then conveyed through an alumina tube in a furnace set to 950°C, where they are decomposed and calcined to form metal oxides. Because the oxides of the refractory metals possess a high saturated vapor pressure, the metal oxides are completely vaporized in the high temperature zone of the furnace (position III). After leaving the furnace and cooling, the metal oxide vapor is re-nucleated into metal oxide nanoparticles (oNPs) ( Figure 1 The use of highly diluted salt solutions allows for easy and accurate control of the input amount of metal sNPs, and precise control of the size of the metal oNPs at position IV.

[0150] To produce a nearly monodisperse population of metal oNPs for collection, the polydisperse metal oNPs from the furnace were first charged using a radioactive charge neutralizer (TSI 3077) and subsequently passed through a DMA (TSI 3085) which selects a very narrow range of particles based on their charge to drag (diameter) ratio. During DMA size selection, the aerosol flow rate was set to 1.5 lpm and the sheath flow of the DMA was set to its maximum value of 20 lpm to produce the narrowest particle size range.

[0151] To collect nanoparticles for substrate-based growth or characterization, the DMA-selected nanoparticles (which are still charged) are fed into an electrostatic precipitator, where they are deflected by an electric field (~50 V / mm) and deposited onto the target substrate (position V). Taking into account the aerosol concentration (c), collection efficiency (δ), aerosol flow rate (v), and substrate size (A), the areal density (n) of oNPs on the substrate can be easily varied by changing the deposition time (t):

[0152] n=cvtδ / A (1)

[0153] NP concentrations before and after the precipitator were monitored by a condensation particle counter (CPC, TSI 3756).

[0154] Substrate-based CVD growth of SWCNTs follows the methods outlined by Yang et al. [supra] and Zhang et al. [supra]. Specifically, oNPs deposited on various substrates in H2 were subjected to a temperature programmed reduction process to obtain solid metal nanoparticles (mNPs). Subsequently, ethanol vapor as a carbon feedstock was introduced into an argon carrier gas into the reaction zone. The H2 flow rate was varied to regulate the carbon-hydrogen (C / H) ratio of the growth environment. After a set growth interval, the hydrogen-rich environment was purged by H2 and then cooled to room temperature.

[0155] Mechanism of particle size selection

[0156] DMA can select a specific particle size between an upper limit of nearly 1 μm and a lower limit of about 1.7 nm. Specifically, DMA classifies particles by charge-to-aerodynamic drag ratio. If the charge state of a particle is known, the drag or "mobility" of the particle and the mobility-equivalent diameter (which is the diameter of a sphere that exhibits the same aerodynamic drag as the particle in question) can be determined. Therefore, for roughly spherical particles, the mobility-equivalent diameter is close to the physical diameter. Mobility can be associated with diameter using the following equation:

[0157]

[0158] Here, B is the mobility (also called mechanical mobility), μ is the gas viscosity, and d m is the mobility-equivalent diameter, and C c is the Cunningham slip correction factor (an empirical relationship that corrects for changes in particle-gas interactions in the transition or free molecular flow regime rather than in the continuum regime). The Cunningham slip correction can be determined as follows:

[0159]

[0160] where λ is the mean free path of the gas molecules. From this, the charge-to-drag ratio or "electrical mobility" (Z) can be calculated from the product of the mechanical mobility and the charge of the particle:

[0161]

[0162] Among them, n q is the number of electric charge (electrons), and e is the elementary charge.

[0163] DMA selects by electrical mobility, which is achieved by first passing the aerosol through a charge neutralizer, which imparts a Weidensolar charge distribution to the particle sample (see Wiedensohler, A. An approximation of the bipolar charge distribution for particles in the submicron size range. Journal of Aerosol Science 19, 387-389, (1988)). The distribution is roughly neutral overall, but contains particles with any number of charges and is also a function of particle size. For very small particles, most are neutral (~98%), and almost all charged particles will have either gained or lost a single electron, while a negligible number of particles will have at least two charges. Subsequently, in the "aerosol stream" Q a The particles are introduced into the annular region between two concentric cylinders of the DMA column (see Fig.10 ). A voltage is applied to the inner cylinder and a sheath gas flow Q sh Particles with opposite charges in the inner cylinder move radially toward the cylinder while simultaneously moving axially down the cylinder. Particles with electrical mobilities above the set point will impact the cylinder and settle there. Particles with lower mobilities will leave with the bulk gas flow and be filtered out. Particles with electrical mobilities matching the set point will enter a small port at the base of the inner cylinder and be "classified" into the sample flow Q. sh Leave DMA.

[0164] Fig.10 The schematic illustration of the DMA column in shows the first to fifth particles, which are identified from left to right as follows. The mobility of the first particle is too high, and it impacts the inner cylinder. The second particle has the recommended electrical mobility and is classified. The migration of the third particle is too low, and it leaves the column in the sheath flow. The fourth particle is neutral and is not affected by the electric field, so it also leaves in the sheath flow. The fifth particle has an incorrect charge polarity and is repelled toward the outer cylinder.

[0165] The performance of the DMA is responsible for the size range of the catalyst particles and therefore the diameter range of the CNTs. The DMA grades the particles according to a triangular transfer function, which means that in theory, 100% of the particles at the recommended size are transmitted through the DMA while particles with larger and smaller diameters than this recommended size are transmitted but with reduced efficiency because their mobility-equivalent diameter deviates from the set point. In practice, particle diffusion leads to some particle losses to the cylinder wall and a small amount of broadening of the transfer function. The minimum electrical mobility (maximum mobility-equivalent diameter) graded by the transfer function can be determined using the following relationship:

[0166]

[0167] where r1 and r2 are the inner and outer cylinder radii, respectively, V is the voltage between the cylinders, and L is the effective length of the cylinder. Similarly, the maximum electrical mobility (minimum mobility - equivalent diameter) classified by the DMA transfer function is equal to

[0168]

[0169] For this example, Q a Equal to Q s , so the peak mobility (Z*) of the transfer function is equal to

[0170]

[0171] If the sheath flow remains constant, it is the voltage between the cylinders that determines the graded electrical mobility. In addition, the gas flow rate determines the width of the transfer function (i.e., the size range of the graded particles). Specifically, the width is determined by the ratio of the sheath gas in the DMA to the sample flow in and out of the DMA. The ratio of the sheath flow rate to the sample flow rate is called resolution and is equal to the normalized half-maximum full width of the transfer function. Therefore, it makes sense to maximize the DMA resolution to produce the narrowest range of catalyst particles. For a triangular distribution, the normalized half-maximum full width will be half of the difference between the maximum and minimum electrical mobilities transmitted divided by the peak electrical mobility:

[0172]

[0173] As can be seen above, when DMA sheath flow is large compared with aerosol / sample flow, particles of the narrowest size range will be classified. Fortunately, electrical mobility is also comparable to the sheath flow rate scale, which means that when the sheath flow is high, maximum electrical mobility and therefore minimum mobility-equivalent diameter can be classified. Thus, both large size range and transfer function resolution are favorable under high sheath flow, so maximizing this value is noteworthy. For this embodiment, the aerosol flow rate is 1.5lpm and the sheath flow is set to 20lpm, corresponding to a resolution of 13.3, which is greater than the standard resolution of 10.

[0174] Although charged particles can be easily fractionated using DMA, it should be determined whether small uncharged particles can migrate through DMA via Brownian motion fast enough to also be fractionated. This phenomenon can be checked by calculating the approximate distance that the particles will be able to diffuse given the time the aerosol spends in DMA. The one-dimensional rms diffusion distance (x rms ) can be determined as follows:

[0175]

[0176] Here, D is the diffusion constant of the particle, and t is the diffusion time. The diffusion constant is equal to

[0177] D=kTB, (S9)

[0178] where k is the Boltzmann constant, T is the temperature, and B is the mechanical mobility defined above. The diffusion time is determined by calculating the velocity within the annular region of the DMA and combining this value with the effective DMA length. The diffusion time (t) in the DMA is

[0179]

[0180] Where L is the DMA length, is the gas velocity, Q is the volume flow rate, A is the annular cross section within the DMA, and r o and r i are the outer and inner radius of the DMA column respectively.

[0181] Using the geometry of the model 3085 DMA, an aerosol flow of 1.5 lpm, a sheath flow of 20 lpm, and air as the carrier gas at standard conditions, a 1 nm particle should diffuse 1.13 mm. Compared to the annular gap distance of nearly 10 mm, this diffusion rate is insufficient to allow neutral NPs to migrate to the target substrate, especially considering that this calculation is one-dimensional and that in reality some of the Brownian motion of the particles will also be in the axial and circumferential directions of the DMA.

[0182] Characterization

[0183] The particle size distribution was analyzed using a Scanning Mobility Particle Sizer Spectrometer (SMPS), which consists of a combination of DMA and CPC. DMA scans through its particle size range, while CPC records the corresponding number concentration (specifically, the mobility-equivalent diameter of the particles) for each size bin. Figure 1 The vertical axis dN / dlogd m represents the number concentration normalized by the bin width. The measured data were fitted using a lognormal distribution, which is standard practice in aerosol science. These give the geometric mean diameter (GMD, peak position), geometric standard deviation (GSD, width) and total number concentration (N) of the sampled aerosols. tot , the area under the distribution).

[0184] AFM was performed on a Veeco Dimension Pro AFM in Peakforce mode.

[0185] HRTEM was performed on a FEI Talos F200X TEM (200 kV for NPs, 80 kV for CNTs) with oNPs collected on Si3N4 grids. The reduction and CNT growth stages were performed in situ on Si3N4 grids before characterization.

[0186] Electron diffraction (ED) of suspended CNTs was performed on a FEI Tecnai F20 FEG TEM operating at 80 kV using STEM nanobeam mode. The Si3N4 grid accompanying the growing CNTs was occasionally punctured to obtain suspended CNTs extending from the substrate.

[0187] For XRD characterization, oNPs were filtered under reduced pressure onto an anodized alumina membrane filter (AAO, Whatman FIL3010). The size of the oNPs was controlled and constrained by the concentration of the aqueous salt solution. The oNPs on the AAO were reduced in H2 to obtain mNPs which were subsequently used for typical CNT growth. XRD characterization was performed at each stage.

[0188] Raman mapping in the RBM range (70-350cm -1) was performed using 532, 638 and 785 nm lasers. Details are presented in Table 1. The laser spot raster scanned randomly oriented CNTs grown on a SiO2 / Si substrate with position markers. The step size was set to 3 μm in both the x and y directions. After removing the background, the peaks of each spectrum in the RBM Raman map were identified and then associated with chirality based on the Kataura diagram (see Kataura, H. et al. Optical properties of single-wall carbon nanotubes. Synthetic Metals 103, 2555-2558, doi: https: / / doi.org / 10.1016 / S0379-6779(98)00278-1(1999)). The abundance statistics obtained by different lasers were normalized by the number of pixels and pixel size.

[0189] Table 1: Experimental details of Raman analysis

[0190] λ(nm) NA Power(mW) Grating(gr / mm) set up 532 0.50 6.35 1800 Horiba Xplora Plus 638 0.50 7.5 1800 Horiba Xplora Plus 785 0.75 10 1200 Bruker Senterra

[0191] It is well known that in order to determine (n,m) based on the Kataura graph, E ii and ωRBM-dt are strongly affected by the environment in which the CNT is located. Using Kataura plots with the correct environmental correction is crucial to obtain reliable identification. Figure 6 The corrected Kataura plot shown in . For all data, the starting point is the experimental data of nanotube optical transitions (transitions) derived from suspended single isolated SWCNTs, which are based on electron diffraction and Rayleigh scattering (see Liu KH et al. An atlas of carbon nanotube optical transitions. Nat. Nanotechnol. 7, 325-329, doi: 10.1038 / Nnano.2012.52 (2012)). iiA red shift of 40 meV was used to correct for environmental interactions between SWCNTs and the silica substrate. The resonance window (broadening factor) was set to 100 meV (see Saito, R., Flofmann, M., Dresselhaus, G., Jorio, A. & Dresselhaus, MS Raman spectroscopy of graphene and carbon nanotubes. Adv. Phys. 60, 413-550, doi: 10.1080 / 00018732.2011.582251 (2011)). Some metallic thin SWCNTs may have larger values ​​due to exciton-phonon coupling (see Doom, SK, Araujo, PT, Plata, K. & Jorio, A. Excitons and exciton-phonon coupling in metallic single-walled carbon nanotubes: Resonance Raman spectroscopy. Phys. Rev. B 78, 165408, doi: 10.1103 / PhysRevB.78.165408 (2008)), which is also considered during (n, m) identification. As for the ωRBM-dt relationship, it follows the reported ωRBM = 235.9 / dt for SWNTs grown on SiO2 / Si substrates. t +5.5 (see Zhang, D. et al. (n,m) Assignments and quantification for single-walled carbonnanotubes on SiO2 / Si substrates by resonant Raman spectroscopy. Nanoscale 7, 10719-10727, doi: 10.1039 / C5NR01076D (2015)).

[0192] like Figure 6 As can be seen, the chiral RBM is located at 155 cm -1 Below (corresponding to diameter ˜1.76 nm) the chirality distribution is dense. Given the resolution of Raman, unambiguous identification becomes impossible. Therefore, only the chiral abundance of SWCNTs with small diameters can be accurately calculated. The peak for large diameters is calculated, but it is not attributed to a specific chirality.

[0193] To illustrate the chirality percentage and the number of identical chiral tubes visible under the same laser spot, the reported method (see Zhang [supra]) was followed for the 0.81 nm (295 cm -1 )-1.53nm(160cm -1 ) range to quantify the percentage of (n,m)SWNTs.

[0194] result

[0195] Figure 1 Aerosol size distributions of Re sNPs, oNPs, and size-selected oNPs are shown at positions II, IV, and V. The nanoparticle size distribution peak position, peak width (independent of height), and total number concentration are expressed by the geometric mean diameter (GMD), geometric standard deviation (GSD), and N tot describe.

[0196] After the solution droplets are dried ( Figure 1 In position II), sNPs have mobility-equivalent diameters of tens of nanometers and a wide distribution. Figure 1 The sNPs are shown to have a GMD of 55 nm and a GSD of 1.83. This distribution is very broad, considering that the log-normal aerosol size distribution has a GSD of approximately 1.4 at equilibrium. These particles are clearly too large and polydisperse for SWCNT growth. Gasification and renucleation in the furnace produce much smaller oxide particles (shown at position IV) in significantly higher concentrations. Compared to the previous sNPs, the oNPs are an order of magnitude smaller in size (GMD of 4.8 nm) and nearly two orders of magnitude more numerous. The distribution is also narrower, with a GSD of 1.38, which is very close to the equilibrium or "self-preserving" size distribution. Given this GMD and GSD, the full width at half maximum of the distribution is 3.7 nm. Therefore, after renucleation, the size of the oNPs is initially constrained. The dominant size of the oNPs can be initially adjusted by varying the concentration of the atomized solution (see Figure 7 ).

[0197] Although the peak size of the oNPs at position IV is much smaller than that of the sNPs in position II, the distribution is still polydisperse. To obtain an even narrower size range, DMA was used at position V with the output distribution set to the recommended GMD of 4.15 nm. The SMPS scan showed excellent agreement with this setting, as the resulting GMD was 4.31 nm. The distribution was extremely narrow (nearly monodisperse), with a GSD of only 1.05. A GSD of 1 represents an infinitely fine distribution of particles in exactly one size (perfect monodisperse).

[0198] After passing through DMA, the FWHM of the size distribution should be 7.5% of the set point. For a set point of 4.15 nm, this corresponds to an extremely narrow FWHM of 0.31 nm. In reality, the distribution is slightly wider and is approximately 0.52 nm. Because the width of the distribution is comparable to the midpoint setting, choosing a smaller size also corresponds to a smaller FWHM.

[0199] The size distribution of NPs was precisely characterized using AFM and TEM. Figure 2 As shown in Figures ac, particles with a narrow size range are uniformly deposited on the target substrate by electrostatic precipitation. The size of the NPs can be varied by varying the DMA set point (see Figure 2 f) and precisely regulated, and smaller DMA set points also correspond to narrower distributions. Regardless of large or small, the size distribution of deposited NPs for SWCNT growth is narrow, and the standard deviation (σ) is at most 0.6nm. Such a narrow distribution as observed in this embodiment is difficult to obtain by other methods, and to date, all other methods are batch processes, which either rely on complex manufacturing techniques, or rely on dedicated expensive precursors, and often rely on specific substrate compositions. The method of the present invention in this embodiment enables continuous production of narrowly distributed nanoparticles that are directly deposited on any substrate.

[0200] At the collection point, the NPs are in the form of oxidized metals ( Figure 8 By HRTEM (see Figure 2 d inset), the oNPs appear to be tightly packed polycrystals. After reduction in H2 at high temperature, the oNPs reconstruct into single crystalline elemental mNPs (see Figure 2 e). Figure 2 HRTEM results of the size distribution of each stage are summarized in f for Mo. Reduction and reconstruction reduced the mNP diameter to ∼60% of the collected oNP diameter ( Figure 2 (Black arrows in f). During carbon growth, the catalyst particles do not show significant changes in diameter compared to the mNPs. The size of the mNPs closely matches the diameter of their corresponding CNTs.

[0201] Figure 3 XRD profiles are shown in c and 8. oNPs were reduced in H2 to obtain mNPs. With the introduction of carbon source, mNPs supported the growth of CNTs. Figure 3 c and 8 show that during the growth process, W and Mo form WC and Mo2C, respectively, while Re remains in its elemental state. Mo2C has an orthorhombic system and space group Pbcn (point group D 2h ). In contrast, WC and Re exhibit hexagonal systems with respective space groups P6m2 (point group D 3h ) and P63 / mmc (point group D6h ). WC, Mo2C and Re have very high melting points, ensuring that they remain in a solid state during growth. Crucially, this feature allows the catalyst to surpass liquid catalysts in terms of their ability to reliably control SWCNT chirality. Maintaining a solid state during reduction and growth also makes size selection more worthwhile compared to that of liquid catalysts because Ostwald ripening is suppressed. About Figure 8 d, The pattern of ReC overlaps with part of the pattern of Al2O3. Therefore, the profiles of Re mNP and Re catalyst with the peak at ~46° are normalized. The two profiles around 61°, 33° and 36° also match Al2O3, thus excluding the presence of ReC.

[0202] During XRD characterization, it is difficult to prevent oNPs (especially Re oNPs) from absorbing water vapor from the environment to form hydrates or weak acids. Sodium ions in oNPs are unavoidable impurities. However, the catalyst is not affected by impurities. During reduction and growth, amorphous AAO is reduced and partially annealed.

[0203] SWCNT growth and catalyst constraints

[0204] Using typical growth parameters, the concentration of SWCNTs was controlled by varying the areal density of deposited oNPs. This was achieved simply by varying the collection time, and the low and high areal density cases were shown to be Figure 3 a and b. Due to the gas phase nature of catalyst formation, the particles are not substrate dependent. A range of substrates can be used to support oNPs for SWCNT growth. Figure 3 a and b), random SWCNTs are grown directly without any ex situ transfer process. Aligned SWCNT arrays have also been synthesized under the guidance of sapphire and ST-cut quartz substrates (see Fig. 9 ).

[0205] like Figure 3 As shown in df, the diameter of the SWCNt is strongly influenced by the size of the mNP and ultimately by its preceding oNP ( Figure 2 f). Most of the SWCNTs grown on a given substrate show similar diameters. These results once again confirm the dominant effect of catalyst size on the resulting SWCNT structure. In the case of ~6.7 nm oNPs (mNPs ~4.5 nm), few-walled CNTs with multiple kinks are the dominant products, with lengths of tens of microns ( Figure 3 f). Using ~4.3 nm oNPs (mNPs ~2.6 nm), longer and higher quality SWCNTs with a diameter of ~3 nm were grown ( Figure 3 e). In the case of ~2.4 nm moNPs (mNPs ~1.4 nm), SWCNTs with a diameter of ~1.5 nm are dominant ( Figure 3 d). With the use of these small and narrowly distributed sizes of oNPs (typically <2.5 nm, mNPs <1.5 nm), good chirality control of SWCNTs was achieved.

[0206] By TEM, CNTs were shown to grow tangentially from the solid catalyst, resulting in a "pea pod" structure (see Figure 3 e and f), where the catalyst maintained its spherical shape without reshaping, a common occurrence for liquid catalysts. It is noteworthy that the catalyst was frequently found to be completely encapsulated by the carbon layer, regardless of whether CNTs were successfully grown ( Figure 3 e, f, and Fig.13 ).

[0207] Chiral constraints from solid catalysts

[0208] The chiral distribution or abundance of SWCNTs is mainly determined by the random distribution of SWCNTs grown on labeled substrates (such as Figure 3 The Raman RBM (radial breathing mode) mapping performed on the surface of the SWCNT (shown in a) is characterized. As an efficient, low-cost and non-destructive characterization method, resonance Raman (RR) spectroscopy remains an indispensable characterization method for the chirality identification of SWCNTs, especially for the large-area statistics of SWCNTs grown on substrates. By 532, 638 and 785nm lasers, SWCNTs with different chirality give excitation responses corresponding to those present in the Kataura diagram (with corresponding environmental factor corrections) and show dependence on the diameter of the RBM peak. By Raman xy-2D mapping, the laser point raster scans the surface and obtains a spectrum for each pixel. This illustrates the abundance of SWCNTs relative to both the number of tubes and the length of each tube, that is, the mass abundance. Compared with the RBM peak height, the mass abundance is more reflected by the frequency of occurrence of the corresponding peak. The peak is extracted from each pixel of the map and presented in a cumulative manner. Figure 4 ac. The statistical abundance of each peak was obtained from each sample using three excitation laser wavelengths ( Figure 4 df) and summarized on the Graphene map ( Figure 4 g).

[0209] In the Kataura diagram (see Figure 6 ), with diameter >1.57nm (RBM peak ~155cm -1 ) are too densely packed to allow unambiguous identification of the chiral index. To ensure unambiguous identification, graphene maps were drawn only for structures with a diameter < 1.57 nm (RBM peak ~155 cm-1 ,Depend on Figure 4 The blue dotted lines in ag represent the abundance values, but the abundance values ​​are based on all possible SWCNTs. For chirality that cannot resonate with 532, 638, and 785 nm lasers, the honeycomb grid is left blank. Chirality near (2n,n) may be enriched, and almost no chirality can exist in the near-zigzag region.

[0210] Nanobeam electron diffraction (ED) was also used to determine the chirality of the CNTs, and the results are summarized in Figure 4 In the graphene map shown in h. Although ED is not effective, it is still the best method to pointlessly identify the (n,m) chiral indices of all possible tubes. ED pattern ( Figure 4 i) From suspended CNTs that occasionally extend from the substrate. Due to this method, the abundance deviates from mass abundance to tube abundance, and information about tube length is missing. However, this technique gives more clues about the tube nucleation conditions, and the preferred chirality near (2n,n) is still visible.

[0211] Depend on Figure 4 g, for W (oNP diameter ~2.5nm, mNP diameter ~1.5nm), the most enriched chirality visible is (12,6), (10,5), (8,4), (12,5), and (9,4), which are located near (2n,n) with a chiral angle of nearly 19.1°. The highest mass abundances of (12,6), (10,5), and (8,4) reach ~30%, ~20%, and ~15% in thin SWCNTs (0.81-1.52nm, the range in which they can be unambiguously identified), and ~20%, ~15%, and ~10% in the 0.81-2nm range. Nearly 90% of all visible (2n,n), (2n±1,n), and (2n±2,n) chirality are found in all thin SWCNTs. In contrast, almost no chirality is identified near the zigzag or chair regions. Only (8,7) and (11,10) have moderate abundances, if their abundances are not overestimated by the neighboring chiralities (10,5) and (13,8), (15,5) and (14,7), respectively (see Figure 6 ). For all the visible (2n,n), (2n±1,n) and (2n±2,n) chiralities (each compared to a tube of similar diameter), only (10,4) and (11,5) are less enriched. The low abundance still seems to originate from the unfavorable resonance conditions, considering the fact that both (10,4) and (11,5) are visible in the ED results with enriched abundance, while the abundance of (10,4) and (11,5) is less than that of (10,4). Located near the edge of the 0.1eV resonance window of 532 or 638nm laser. (11,5) It also seems to resonate poorly with 532nm lasers.

[0212] As for the ED results, a concentrated distribution with diameters less than 1.3 nm can be seen, which explains the low abundance of (13,6), (14,7), and (16,7) compared with (12,6), (10,5), and (8,4). Figure 4 df). As mentioned above, ED reveals information about the number of tubes and therefore the conditions of tube nucleation. Based on the results, tubes with a chiral angle of 19±5° are still enriched. Although some zigzag tubes appear, no chair tubes are identified. The appearance of zigzag tubes is attributed to enrichment during nucleation. Compared to Raman RBM mapping, the wider chirality distribution from ED can be explained by the recently reported A|Z separation at the interface of solid catalyst-tubes, which greatly reduces the interfacial energy of all chiral tubes, thereby broadening the equilibrium CNT nucleation probability distribution.

[0213] Compared with WC, Mo2C and Re show a similar trend of producing more near (2n,n) chirality ( Fig.11 el), but also exhibit some different chiral preferences. Compared to WC, Mo2C produces moderate abundances of (8,5), (9,6), (14,4), and (13,4), while producing less (7,6), (10,6), and (8,4). For Re, there are more (9,4), (11,4), and (12,5) but less (8,5). Solid-state catalysts and similar CVD parameters lead to products enriched in more near (2n,n) tubes. However, differences in tube-catalyst interfacial energies and therefore nucleation and growth differences lead to slight differences between these catalysts. In fact, this work represents the first chirality-controlled growth of SWCNTs from Re, which uniquely remains elemental and solid after growth.

[0214] As mentioned above, the point groups of WC, Mo2C, and Re are different, corresponding to 3-fold, 2-fold, and 6-fold symmetries, respectively. However, based on the statistics of the experimental results, WC, Mo2C, and Re produce more SWCNTs close to (2n,n), and the least detected chirality is always located towards the zigzag (ZZ) and chair (AC) regions in the graphene map ( Figure 4 Middle W, and Fig.11 The symmetry of the catalyst appears to have a limited effect on the abundance of SWCNT chirality.

[0215] In addition to the requirement for a solid catalyst, the carbon to hydrogen ratio also appears to be important for chiral selection. In the case of excess carbon supply (C:H>1:15), the chiral selection is clearer, with (12,6) and (10,5) always dominating and all chirals located near the (2n,n) line. In contrast, when C / H<1:5 (see Fig.12 ), the chirality control is less clear. A variety of other chiralities are observed in abundances comparable to those near the (2n,n) line.

[0216] Based on the growth results, optimal chirality control can only be achieved when the catalyst size is small enough (typically where the oNP diameter is <3 nm). Larger diameter catalysts produce more tubes with larger diameters, which results in more chirality. Furthermore, tangential growth is dominant, and HRTEM has verified a highly positive correlation between catalyst and SWCNT diameter (see Figure 3 and 13 ). By remaining solid during growth, the catalyst maintains a fixed diameter, which is critical for achieving chirality control.

[0217] Furthermore, unlike Fe, Co and Ni catalysts, solid W, Re and Mo catalysts have relatively low oxidation temperatures in air, allowing them to be easily removed after CVD, leaving pure CNTs on the target substrate.

[0218] Qualitative Modeling

[0219] Without requiring a symmetry matching mechanism to understand the observed preferred chirality distribution, factors such as tube-catalyst interface thermodynamics during nucleation, growth kinetics, and self-developed chirality-dependent growth time were investigated.

[0220] As reported in Artyukhov [supra], the mass-based abundance of (n,m) SWCNTs at time t is given by the following integral:

[0221]

[0222] where p(τ,n,m) and n(τ,n,m) are the cumulative probability and growth rate of the catalyst growing (n,m) SWCNTs at time t, respectively. Based on the assumption that the growth time is independent of chirality, all time terms are separated from the chirality-dependent term (n,m) in Equation 2 as follows:

[0223] A(t,n,m)=N(n,m)R(n,m)S(t) (3)

[0224] where N(n,m) is the probability of nucleation of (n,m)SWCNT from the catalyst, R(n,m) is the growth rate of (n,m)SWCNT, and S(t) is the set of all time terms.

[0225] However, equation 3 is only valid if the catalyst deactivation is independent of chirality or if the catalyst is always active and therefore the length of the CNT will be governed only by the growth rate. However, after CNT synthesis, deactivated catalysts are always observed to be accompanied by relatively short CNTs (see Fig.13 ). Catalyst deactivation can result from increasing surface carbon that is not effectively delivered to feed SWCNT growth. Figure 3 As shown in e and f, the catalyst is always surrounded by a carbon cap, resulting in a "pea pod" morphology. This phenomenon can be more pronounced when an inefficient solid catalyst is used instead of an efficient liquid catalyst (like iron).

[0226] In addition, differences in growth kinetics can lead to catalyst deactivation as a function of chirality. Only chirality with sufficient growth rate can incorporate incoming carbon towards CNT growth rather than surface accumulation and catalyst poisoning. Thus, in addition to the faster growth rate, these chiralities will also be able to extend their growth time before the growth time is interrupted by catalyst poisoning. If the growth rate of a particular chirality is fast enough, the carbon supply rate will be the limiting factor for CNT growth rate and CNT length. In short, the growth time difference factor dependent on chirality will be distinguished from the growth kinetic factor.

[0227] Here, the phenomenon involved is the capture rate R 捕捉 , which is proportional to the rate of incident carbon onto the catalyst (to feed or hinder CNT growth). Another parameter is the carbon tolerance capacity of the catalyst, U(d). Knowing that the catalyst is solid during growth and that carbon surface diffusion is the dominant growth mode rather than bulk diffusion, it is assumed that U(d) is proportional to the catalyst surface area. Then the abundance of (n,m) SWCNTs at time t will be modified to:

[0228] A(t,n,m)=N(n,m)V(n,m,t) (4)

[0229] Here, V(n,m,t) is the growth rate term and accounts for the chirality-dependent growth time, where

[0230]

[0231] where t is the growth time set during the experiment. In addition, when t is long enough, the occasional random end of CNT growth due to formation defects, etc., will form an upper bound on t.

[0232] V(n,m,t) summarizes whether growth is constrained by either carbon supply (Eq. 5.1), growth time (Eq. 5.2), or catalyst carbon tolerance (Eq. 5.3).

[0233] Additional modeling details related to abundance calculations are provided in the Appendix below. When the C:H ratio is low, SWCNT growth can be constrained by carbon supply (Eq. 5.1) (the exceptions are zigzag and chair SWCNTs, for which the growth rate is too low). In this case, any differences in nucleation preference will dominate the resulting chiral distribution. For solid catalysts, the thermodynamic preference is mainly driven by different catalyst-tube interface energies. As mentioned above, the recently reported A|Z separation at the interface greatly reduces the interface energy of all chiral tubes and broadens the equilibrium CNT nucleation probability distribution. Growth will end at a set time or randomly by defects.

[0234] In contrast, when the growth environment is carbon-rich, SWCNTs with low growth rates will lead to catalyst poisoning much earlier, leaving only the fast-growing chiralities to continue growing and resulting in a higher mass-based abundance of these fast-growing chiralities in the product. On solid catalysts, the growth rate is bimodal, with minima at the AC and ZZ ends and a maximum at the 19.1° line for (2n,n) SWCNTs (see Fig.14 e). Therefore, the abundance distribution will prefer (2n,n), (2n±1,n) and (2n±2,n) chirality (see Fig.14 h), and this confirms the experimental abundance results.

[0235] In addition to nucleation thermodynamics, growth kinetics, and chirality-dependent growth time, the size of the catalyst directly determines the region of possible chirality, thereby affecting the final chiral abundance ( Fig.14 fg is compared with hi).

[0236] Growth from liquid catalysts has also been modeled and presented in Fig.14 ac. Using the same set of modeling parameters, AC and near-AC SWCNTs are preferred, mainly due to the fact that the growth rate is proportional to the chiral angle. However, due to Ostwald ripening, liquid catalysts tend to have a wider size distribution than solid catalysts, which in turn leads to a wide distribution of SWCNT diameters and chirality. In the case of very low energy barriers, SWCNT nucleation from liquid catalysts will also be indiscriminate.

[0237] in conclusion

[0238] Due to the gas phase nature of the catalyst formation process, the particles are not substrate dependent. Therefore, the substrate can be completely eliminated to achieve a fully continuous process. By having the hydrogen and carbon sources in the gas line, continuous floating catalyst CVD (FCCVD) growth from solid catalysts has been achieved for the first time (see Figure 5 ). Figure 5 b and c show some preliminary products from FCCVD using W solid catalyst. To increase the CNT production rate, FCCVD growth was performed using large catalysts (oNPs>5nm) without fine size selection. The relatively low efficiency of solid catalysts compared to traditional liquid catalysts, the sensitivity of refractory metal oxides to reduction processes, and the lack of carbon transfer from the substrate to the catalyst are more of a challenge.

[0239] A highly scalable method for producing nearly monodisperse W, Mo, and Re oxide nanoparticles with diameters less than 2 nm was achieved through an aerosol-based size selection approach.

[0240] These nanoparticles are reduced to form a solid catalyst capable of producing well-controlled CNT diameter and chirality distributions. While symmetry matching and epitaxial growth are well known, the chirality control mechanism is attributed not only to differences in growth rates between chiralities, but also to differences in the extended growth times available for fast-growing CNTs. In the case of a high-carbon growth environment, the three metals produce similar (2n,n) chiral SWCNTs, with particularly high abundances of (12,6) and (10,5). The chirality with a chiral angle of 19±5° is particularly dominant, reaching an abundance of over 90%. With the help of an aerosol method that produces NPs with precise sizes, the continuous production of chirality-controlled SWCNTs can be achieved and can help increase the impact of this attractive material in multiple scientific and engineering fields.

[0241] appendix

[0242] As reported by Artyukhov [supra], at time t, the abundance of (n,m) SWCNTs is given by the integral:

[0243]

[0244] Where p(t,n,m) and v(t,n,m) are the cumulative probability and growth rate of (n,m) SWCNTs grown from this catalyst at time t.

[0245] As mentioned above, if the chirality-dependent growth time difference is taken into account, the abundance of (n,m) SWCNT at time t is modified to:

[0246] A(t,n,m)=N(n,m)V(n,m,t) (Eq.4)

[0247] Here N(n,m) is the probability of nucleation of an (n,m) SWCNT from the catalyst, V(n,m,t) is the growth rate term, and accounts for the chirality-dependent growth time, where

[0248]

[0249] where t is the growth time set during the experiment. V(n,m,t) summarizes whether the growth is constrained by any of the following: carbon supply (Eq. 5.1), growth time (Eq. 5.2), or catalyst carbon tolerance (Eq. 5.3). R 捕捉 is the capture rate, which is proportional to the rate of incident carbon onto the catalyst. U(d) is the carbon tolerance capacity of the catalyst, d is the SWCNT diameter. R(n,m) is the growth rate of (n,m) SWCNT.

[0250] As reported in Artyukhov [supra], the thermodynamic model during nucleation is as follows:

[0251]

[0252] where Γ n,m is the contact interface energy between the CNT edge and the catalyst, and For the cap free energy.

[0253]

[0254] Here, is the CNT-catalyst interaction energy of A or Z type edge atoms.

[0255]

[0256] is the bending rigidity of graphene, and d is the diameter of (n,m) SWCNT.

[0257]

[0258] Here, is the elastic energy of the CNT cap, which is a constant for the hemispherical elastic shell. and are the cap entropy and the number of (n,m) chiral SWCNT caps, respectively. B is the Boltzmann constant.

[0259] At the CNT-solid catalyst interface, re-structured asymmetric CNT edges (separated A|Z-edges) and chirality-dependent defect formation have been reported by theoretical modeling. Previous results showed that tubes with 2m < n preferentially nucleate, but chiral tubes with n ≤ 2m grow much faster, greatly releasing the unfavorable nucleation of chiral SWCNTs. The latter results further clarify that the (12,6) A|Z-separated interface is the least prone to defect formation and acts as a "transient attractor" in the chiral evolution trend from Z to A. Here, due to the reported separated A|Z edges, only the cap entropy is considered, without adding the interface configuration entropy.

[0260] However, due to the lack of dynamic Monte Carlo (kMC) simulation capabilities, a conventional circular edge interface is used, which leads to abundances similar to the kMC results without chirality switching. The missing chirality switching from defect formation will even increase the abundance of (2n,n) tubes.

[0261] For the solid catalyst, use and per atom following the reported values from the Co7W6 solid catalyst on the W grid. For the liquid catalyst, use and per atom, which are reported for the Co(111) catalyst with a separated A|Z interface. As Fig.14 shown in a, for a liquid catalyst with a given value, the nucleation thermodynamics will lead to a concentrated chirality with a large chiral angle. For a solid catalyst with a given Fig.14 value, the nucleation tends to prefer a smaller chiral angle but a wider distribution (see

[0262] d).

[0263]

[0264] And

[0265] Regarding the growth kinetics, due to the lack of dynamic Monte Carlo (kMC) simulation capabilities, a conventional circular edge interface is used, and the growth rate R(n,m) is as follows: Fig.14 For a liquid catalyst based on the screw dislocation theory, the consumption of generating a pair of kinks on the A edgeb) For the combination of nucleation thermodynamics and growth kinetics results, the preferred region is near the chair chirality (see Fig.14 c). The abundance is primarily determined by the growth kinetics and results in a wider distribution of chiralities where the chiral angle is large.

[0266] However, on solid surfaces, a pair of kinks is generated that destroys the perfect contact between CNT and substrate. and Both have significant magnitudes, and the dependence becomes bimodal, with minima at the ends of A and Z and a maximum at 19.1° (see Fig.14 e). The combined effect on abundance prefers (n,1) and (n,2) chirality (see Fig.14 f).

[0267] In the case of catalyst size selection, the abundance distribution is shifted due to the guidance effect from the catalyst (see Fig.14 g) Furthermore, when the catalyst is too large, the resulting CNTs will contain more multi-walled CNTs, which destroys chirality control.

[0268] In the case of a carbon-rich environment, a chirality-dependent growth time factor is employed. Fig.14 e sets a threshold. In an embodiment, at a given In the case of the numerical value, if the chirality of ~1 / 2 is set in the range of 0.65-2nm to be restricted, the abundance distribution shifts toward 19.1° and is significantly enriched in (12,6) (see Fig.14 h).

[0269] In case of even narrower distribution and finer catalyst size (0.8 ± 0.2 nm) and appropriate restriction of growth time for some slow-growing SWCNTs, it is expected that semiconducting chiralities such as (8,4), (10,3), (9,4), (11,3) will be enriched (see Fig.14 i).

Claims

1. A method for producing a carbon material comprising SWCNTs, wherein the method comprises: (a) generating a stream of refractory metal material suspended in a carrier gas, wherein the stream of refractory metal is generated by an aerosolization device, the aerosolization device being a solution atomizer; (b) introducing a stream of the refractory metal material into a temperature-controlled flow-through furnace; (c) subjecting the stream of refractory metallic material to temperatures sufficient to generate a stream of nanoparticulate refractory metallic material, wherein the stream of refractory metallic material is exposed to a first temperature zone sufficient to vaporize the refractory metallic material and a second temperature zone downstream of the first temperature zone, wherein the second temperature zone is sufficient to re-nucleate the refractory metallic material to generate the stream of nanoparticulate refractory metallic material; (d) separating a discrete stream of nanoparticulate refractory metallic material exhibiting a selected nanoparticle size distribution from the stream of nanoparticulate refractory metallic material; (e) introducing the discrete stream of the nanoparticulate refractory metal material into a temperature controlled reactor; (f) releasing a stream of reducing agent into the temperature controlled reactor, wherein the stream of reducing agent and the discrete stream of nanoparticulate refractory metal material are exposed to a third temperature zone sufficient to generate the stream of nanoparticulate refractory metal; (g) releasing a stream of a carbon source into the temperature-controlled reactor; and (h) exposing the nanoparticulate refractory metal and carbon source to a fourth temperature zone sufficient to produce the SWCNT-containing carbon material, which may be adapted into a supported or self-supporting form or may be collected from the temperature-controlled reactor; The refractory metal material is a refractory metal compound. wherein step (a) comprises: (a') atomizing a liquid preparation of the refractory metal compound, wherein the liquid preparation of the refractory metal compound is a refractory metal salt solution and the concentration of the refractory metal salt solution is 1.0 mM or less relative to metal atoms, wherein the refractory metal is one or more of the group consisting of W, Mo, Re, V, Nb, Ir, Ru, Os and Rh, wherein the geometric mean diameter GMD of the nanoparticulate refractory metal material in the discrete stream of nanoparticulate refractory metal material is in the range of 1 to 5 nm, wherein the refractory metal material is a refractory metal oxide, wherein the geometric mean diameter GMD of the nano-particulate refractory metal is 2 nm or less, wherein the geometric standard deviation (GSD) of the diameter of the nano-particulate refractory metal material is less than 1.1, wherein the reducing agent is hydrogen, wherein C:H>1:15 and C:H is the carbon:hydrogen ratio in the stream of carbon source and the stream of reducing agent, The refractory metal compound is decomposed and calcined in the first temperature zone to form a refractory metal oxide.

2. The method of claim 1, wherein the refractory metal is W, Mo or Re.

3. The method of claim 1 or 2, wherein step (d) is performed by classifying the nanoparticles of the nanoparticulate refractory metal material according to their mass, aerodynamic diameter or electrical mobility.

4. A method as claimed in claim 1 or 2, wherein the geometric mean diameter (GMD) of the nanoparticulate refractory metal species in the discrete stream of nanoparticulate refractory metal species is in the range of 1 to 3 nm.

5. The method of claim 1 or 2, wherein the number concentration of the nanoparticulate refractory metal material in the discrete stream of nanoparticulate refractory metal material is 10 7 cm -3 or higher.

6. The method of claim 1 or 2, wherein the nanoparticulate refractory metallic species in the discrete stream of nanoparticulate refractory metallic species is substantially monodisperse.

7. The method of claim 1 or 2, further comprising in step (e): (e') introducing a second discrete stream of nanoparticulate refractory metal material into the temperature controlled reactor.

8. An assembly for producing a carbon material comprising SWCNTs according to the method of any one of claims 1 to 7, wherein the assembly comprises: (A) an aerosolization device for generating an aerosol flow of a refractory metal material suspended in a carrier gas, wherein the aerosolization device is a solution atomizer; (B) a temperature controlled flow-through furnace operatively connected to and downstream of the aerosolization device, wherein, in use, the temperature controlled flow-through furnace receives a flow of refractory metal material and discharges a flow of nanoparticulate refractory metal material; (C) a particle size classifier operatively connected to and downstream of the temperature controlled flow-through furnace, wherein, in use, the particle size classifier separates discrete streams of nanoparticulate refractory metal material according to a selected particle size distribution; and (D) a temperature-controlled reactor operatively connected to the particle size classifier and located downstream of the particle size classifier, wherein, in use, the temperature-controlled reactor receives a discrete flow of nanoparticulate refractory metal material, a flow of a reducing agent, and a flow of a carbon source, thereby producing a carbon material comprising SWCNTs.

9. A process for producing a carbon material comprising SWCNTs, wherein the process comprises: (1) generating a flow of a refractory metal material suspended in a carrier gas, wherein the flow of the refractory metal is generated by an aerosolization device, wherein the aerosolization device is a solution atomizer; (2) introducing a flow of the refractory metal material into a temperature-controlled flow furnace; (3) subjecting the stream of refractory metal material to temperatures sufficient to generate a stream of nanoparticulate refractory metal material, wherein the stream of refractory metal material is exposed to a first temperature zone sufficient to vaporize the refractory metal material and a second temperature zone downstream of the first temperature zone, wherein the second temperature zone is sufficient to re-nucleate the refractory metal material to generate the stream of nanoparticulate refractory metal material; (4) separating a discrete stream of nanoparticulate refractory metal material exhibiting a selected nanoparticle size distribution from the stream of nanoparticulate refractory metal material; (5) exposing the reducing agent and the discrete stream of the nanoparticulate refractory metal material to a third temperature zone sufficient to produce the nanoparticulate refractory metal; as well as (6) exposing the carbon source and the nanoparticulate refractory metal to a fourth temperature zone sufficient to produce the SWCNT-containing carbon material, wherein the process further comprises depositing the nanoparticulate refractory metal onto a substrate after step (5); The refractory metal material is a refractory metal compound. The step (1) comprises: atomizing the liquid preparation of the refractory metal compound, wherein the liquid preparation of the refractory metal compound is a refractory metal salt solution and the concentration of the refractory metal salt solution is 1.0 mM or less relative to metal atoms, wherein the refractory metal is one or more of the group consisting of W, Mo, Re, V, Nb, Ir, Ru, Os and Rh, wherein the geometric mean diameter GMD of the nanoparticulate refractory metal material in the discrete stream of nanoparticulate refractory metal material is in the range of 1 to 5 nm, wherein the refractory metal material is a refractory metal oxide, wherein the geometric mean diameter GMD of the nano-particulate refractory metal is 2 nm or less, wherein the geometric standard deviation (GSD) of the diameter of the nano-particulate refractory metal material is less than 1.1, wherein the reducing agent is hydrogen, wherein C:H>1:15 and C:H is the carbon:hydrogen ratio in the stream of carbon source and the stream of reducing agent, The refractory metal compound is decomposed and calcined in the first temperature zone to form a refractory metal oxide.

10. An apparatus for producing a carbon material comprising SWCNTs according to the process of claim 9, wherein the apparatus comprises: (A) an aerosolization device for generating an aerosol flow of a refractory metal material suspended in a carrier gas, wherein the aerosolization device is a solution atomizer; (B) a temperature controlled flow-through furnace operatively connected to the aerosolization device and located downstream of the aerosolization device, wherein, in use, the temperature controlled flow-through furnace receives a flow of the refractory metal material and discharges a flow of nanoparticulate refractory metal matter; (C) a particle size classifier operatively connected to and downstream of the temperature controlled flow-through furnace, wherein, in use, the particle size classifier separates discrete streams of nanoparticulate refractory metal material according to a selected particle size distribution; (D) a first device for exposing a reducing agent and the nanoparticulate refractory metal material to a temperature sufficient to produce the nanoparticulate refractory metal; as well as (E) a second means for exposing a carbon source and the nanoparticulate refractory metal to a temperature sufficient to produce the SWCNT-containing carbon material, The apparatus further comprises: a precipitator operatively connected to the particle size classifier and located downstream of the particle size classifier, wherein when in use, the precipitator deposits the nano-granular refractory metal material onto a substrate; or the precipitator operatively connected to the first device and located downstream of the first device, wherein when in use, the precipitator deposits the nano-granular refractory metal onto a substrate.

Citation Information

Patent Citations

  • Methods of making and purifying carbon nanotubes

    CN105836726A

  • Carbon nanotube synthesis using refractory metal nanoparticles and manufacture of refractory metal nanoparticles

    US20100075137A1